A case of mistaken identity – reappraisal of the species of canid and felid hookworms (Ancylostoma) present in Australia and India - Traub, Rebecca J.; Hobbs, R.P.; Adams, P.J.; Behnke, Jerzy M.; Harris, Philip D.; Thompson, R.C.A. (Cambridge University Press, 2007)
This study serves to clarify the current status of canid and felid Ancylostoma species present in Australia. The morphological identification of A. ceylanicum from cats for the first time in Townsville, Australia, appears to be in error, together with the genetic markers provided for the species. Morphological and genetic data presented herein provide strong evidence that the hookworms from cats in Towsville are not A. ceylanicum as previously identified (i.e. the first report of this species in Australia), but are A. braziliense. Therefore the subsequent genetic markers established for A. ceylanicum in subsequent molecular studies based on these Townsville specimens should also be attributed to A. braziliense. Based on this information, a study of canine hookworm species present in northern India is also in error and it is apparent that the hookworms found in this region are those of A. ceylanicum. The distribution of A. braziliense and A. ceylanicum in the Americas and Asia Pacific region is discussed together with the importance of combining parasite morphology with genetic data for parasite diagnosis in epidemiological studies.